Silent struggles: a qualitative study exploring mental health challenges of undergraduate healthcare students - Shahd Al-Najdi; Abdulla Mansoor; Ola Al Hayk; Najah Al-Hashimi; Kamran Ali; Alaa Daud (BMC Medical Education)
Abstract Background Mental health is a critical aspect of overall well-being, influencing how individuals think, feel, and perform. Mental health among healthcare students has become a major concern, drawing attention due to its profound impact on their welfare, academic performance, and ability to effectively interact with patients. This paper aimed to explore the experiences of undergraduate healthcare students facing mental health challenges at Qatar University. With a focus on understanding the factors contributing to mental health issues and exploring their coping mechanisms, the research also sought to identify students’ recommendations for institutional support to improve their mental well-being. Methods A qualitative approach using semi-structured face-to-face interviews was employed to collect data. A purposive sampling method was used to recruit students from five healthcare disciplines- Medicine, Dentistry, Pharmacy, Health Sciences and Nursing- who had self-reported mild to moderate depressive symptoms based on the Patient Health Questionnaire (PHQ-9) and Depression Anxiety and Stress Scale (DASS21). A total of 15 interviews were conducted, recorded, and transcribed verbatim, with thematic analysis used to identify key themes. Results Several themes emerged from the interviews, including academic pressure, social isolation, anxiety, coping mechanisms, fear of failure, and stigma surrounding mental health support. Academic pressure was consistently reported as a major stressor, contributing to anxiety and emotional strain. Social isolation further exacerbated mental health challenges, while many students highlighted a lack of well-established coping strategies. Stigma related to seeking mental health support was a significant barrier, preventing students from accessing available services. Conclusion The study highlights the mental health challenges faced by healthcare students, emphasizing the need for effective institutional mental health support. Addressing academic pressures, enhancing self-coping mechanisms and social support systems, and reducing the stigma around mental health care are essential steps toward improving student well-being. Clinical trial number Not applicable.